Scheduling of ornamental plant production - Schmidt, G.; Kardos, G.; Szántó, M. (International Journal of Horticultural Science, 2000)
The production of ornamental plants represents an important branch of our horticulture. The growing area is relatively small (round 2800 ha), the production value, however, a rather large. Notwithstanding, its financial balance is inactive because the demand surpasses the supply copiously.The most popular plants are as follows: carnation, gerbera, rose, bulbous flowers, chrysanthemum, other cutflowers, cutgreens and Gypsophyla — their total production value makes up to Ft 8-9 billion. The area of ornamental nurseries — about 800-900 ha — is to be found mostly on the western part of our country.Our accession to the EU will have undoubtedly an impact on our ornamental plant production. We must take into account, that in greenhouse production the specialization extends all over the world, field production over a limited region. Our chances will not deteriorate by joining the EU. The buyer — chiefly because of ecological purposes — will prefer the domestic product to the foreign one. By the way, our products will be competitive, as far as quality or price is concerned, with those of western Europe. Last but not least, we may hope a greater saleability of home-bred, special varieties and cultivars, the so-called "hungaricums", both in the domestic as well as export markets. It is anticipated that we will have a good turnover with potted ornamental plants and flower seedlings. Our nursery products will become marketable too.To exploit the opportunity, of course, the necessary conditions are to be created. First of all, we need development in research, with special regard to breeding, at the same time in education, in extension service, in the training of experts, on a high level. Some tasks can be solved, no doubt by improvement of the organisation within the branch. At the same time the state subsidy is indispensable in order to promote both the technical and the research activities. State subsidy is also necessary to build up more advantageous conditions of sales like in some foreign countries (e.g. the Netherlands).